The business of genocide : the SS, slave labor, and the concentration camps - Allen, Michael Thad. (Chapel Hill, N.C. : University of North Carolina Press, 2002)
An exploration of the bureaucrats behind the Nazi slave labour camps. It contradicts the assumption that the SS forced slavery upon the German economy, demonstrating that instead industrialists actively sought out the Business Administration Main Office as a valued partner in the war economy.
Acknowledgments; Abbreviations; Introduction; 1. Origins of the SS; 2. A Political Economy of Misery; 3. Manufacturing A New Order; 4. Engineering a New Order; 5. My Newly Erected House; 6. The Hour of the Engineer; 7. Total War and the End in Rubble; Epilogue; Notes; Bibliography; Index.
Includes bibliographical references (pages 347-365) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: Nationalsozialistische Deutsche Arbeiter-Partei. -- SS-Wirtschafts-Verwaltungshauptamt -- History; Nationalsozialistische Deutsche Arbeiter-Partei. -- SS-Wirtschafts-Verwaltungshauptamt; Wirtschafts-Verwaltungshauptamt.; World War, 1939-1945 -- Conscript labor -- Germany; World War, 1939-1945 -- Concentration camps -- Germany; Genocide -- Germany -- History -- 20th century; Holocaust, Jewish (1939-1945); Forced labor -- Germany -- History -- 20th century; Holocaust, Jewish (1939-1945) -- Germany; Guerre mondiale, 1939-1945 -- Travail obligatoire -- Allemagne; Guerre mondiale, 1939-1945 -- Camps d'internement -- Allemagne; Holocauste, 1939-1945.; Travail forcé -- Allemagne -- Histoire -- 20e siècle.; Holocauste, 1939-1945 -- Allemagne; HISTORY -- Holocaust; Internment camps; Forced labor; Genocide; Germany; Kriegswirtschaft; Wirtschaft; Zwangsarbeit; Drittes Reich; Konzentrationslager; Deutschland; NSDAP; Concentratiekampen; Dwangarbeid; SS; Bedrijfsleven; Genocide; Holocaust, 1939-1945 -- Germany; 1900-1999; History